Impact of a pharmacoinvasive strategy when delays to primary PCI are prolonged. Issue 9 (17th February 2015) - Gershlick, Anthony H; Westerhout, Cynthia M; Armstrong, Paul W; Huber, Kurt; Halvorsen, Sigrun; Steg, Philippe Gabriel; Ostojic, Miodrag; Goldstein, Patrick; Carvalho, Antonio C; Van de Werf, Frans; Wilcox, Robert G
Abstract : Objectives: Primary percutaneous coronary intervention (P-PCI) is the preferred reperfusion option in ST-elevation myocardial infarction, but its benefits become attenuated as time to its potential delivery becomes prolonged. Based on the STrategic Reperfusion Early After Myocardial Infarction trial, we assessed the impact of increasing time delay on outcomes in patients randomised to a pharmacoinvasive strategy (PI) or P-PCI. Methods: Thirty-day clinical outcomes were examined according to PCI-related delay (P-RD). Data from hospitals that enrolled >10 randomised patients were used and P-RD categorised as ≤55 min, >55–97 min and >97 min. Results: Composite of death/congestive heart failure/cardiogenic shock/myocardial infarction in PI and P-PCI arms occurred in 10.6% versus 10.3% (≤55 min, p=0.910); 13.9% versus 17.9% (>55–97 min, p=0.148) and 13.5% versus 16.2% (>97 min, p=0.470), respectively. While there was no worsening of outcomes for PI across the P-RD spectrum, this occurred in the P-PCI arm (p(trend)=0.038). For P-RD ≤55 min, fewer events tended to occur with P-PCI than PI. Conversely, as P-RD increased to >55 min, PI-assigned patients had better outcomes than P-PCI, suggesting an event-free advantage with PI as P-RD increased (p(interaction)=0.094). Analysing P-RD continuously showed that for every 10-min increment there was an increasing trend towards benefit among PI-assigned patients (p(interaction)=0.073). Conclusions: As P-RD increased, PI outcomes became superior to P-PCI when P-RD is prolonged and exceeds guideline-mandated times. In such circumstances, a PI strategy may provide an alternative reperfusion option. Adverse time delays for delivery of P-PCI should be considered when evaluating reperfusion strategies. Trial registration number: NCT00623623.